Democracy as a global determinant factor to legitimate governance and self-determination - Ahmad, Rusniah; Mohd Sani, Mohd Azizuddin; Efevwerhan, David I. (Benson Idahosa University, 2011)
In the world today, governments come to power, hoping to be embraced by the international community, so they can engage in the usual international intercourse, since no nation can be an island to itself. Sometimes however, some government meet a cold shoulder from the comity of nations because the government is not legitimate. What then determines the legitimacy or otherwise of a government? This paper identifies democracy as the seemingly worldwide accepted means of legitimately assuming political power.It traces the origin of the acceptability of the concept to election monitors in colonial times in other to determine the legitimacy of the decolonisation process of colonies. It then examines how the UN, regional bodies, Western States, third world countries and even some former Communist States have all embraced democracy-the current democratic struggle in the Arab world inclusive; and concludes that what started as a Western concept or ideology is now the preferred means by which nations exercise the right to self-determination.